Evaluation of Single Lead ECG Quality Based on Electrode Features and Positioning - Lempinen, Milja (My University, 2024)
Wearable devices for heart rate and ECG monitoring have been gaining popularity in the last two decades. The wearable market is still growing and looking into the quality and the reliability of the devices is ever so important. The aim of this thesis is to observe how reliable different setups of wearable, single lead ECG devices are, and how the electrodes and their placement affect the resulting signals. The research questions were answered with literature review and laboratory experiments conducted for this thesis. In the experiments, a total of six different setups of three different single lead ECG signal collection devices were observed. The setups had differing electrode materials, distances, or sizes. The main interest points in the produced signals were the amplitudes and waveform quality. The results were evaluated with statistical methods, including visualisations of the signals. The results and conclusions were, that altering the electrode material, distance, or size of the signal collection setup affects the resulting signal. The electrode material affects the signal quality the most, while the distance and the electrode size affect the average waveforms. The results presented in this thesis do not contradict any previous research on the same topic but do support their conclusions gathering the different alterations in the same reference framework.

Puettavien sykemittareiden ja EKG-monitorien suosio on kasvanut viimeisen kahden vuosikymmenen aikana merkittävästi. Puettavien laitteiden markkina kasvaa yhä edelleen ja siksi onkin erityisen tärkeää selvittää näiden laitteiden tuottamien signaalien luotettavuuteen ja laatuun. Tämän diplomityön tavoitteena on tarkastella erilaisten yksikanavaisten laiteasetelmien luotettavuutta ja sitä, kuinka elektrodien materiaalit ja asettelu vaikuttavat signaaliin. Tutkimuskysymyksiin haettiin vastauksia kirjallisuudesta ja työtä varten toteutettujen mittausten tuloksista. Näissä mittauksissa kerättiin dataa yhteensä kolmesta eri laitteesta ja kuudesta eri laiteasetelmasta. Laiteasetelmat erosivat toisistaan elektrodien materiaalin, etäisyyden, tai koon osalta. Pääasialliset tarkastelukohteet olivat signaalien amplitudit ja aaltomuotojen laatu. Mittausten tuloksia arvioitiin käyttämällä tilastollisia menetelmiä sekä visualisoimalla tuloksia. Työn johtopäätöksenä on, että muutokset elektrodien materiaalissa, etäisyydessä, tai koossa vaikuttavat EKG-signaaliin. Eri laiteasetelmien tuottamat signaalit eroavat toisistaan osittain merkittävästikin. Elektrodien materiaali vaikuttaa erityisesti signaalin laatuun, kun taas etäisyys ja koko vaikuttavat aaltomuotoon. Työn tulokset tukevat aiempaa tutkimusnäyttöä, ja eri lähteistä nousseet tulokset ja asetelmat on koottu yhteen kokonaisuuteen yhdistettynä tässä työssä tehtyihin mittauksiin.
Keywords: ECG, heart, monitoring, health technology, biosignals, wearables